Determination of the Critical Level and Development of Phosphorus Fertilizer According to the Soil Test in the Rape Dry Farming of Canola (Brassica napus L) - Nejad, Ebrahim. Fatahi (Recent Progress in Plant and Soil Research Vol. 1, 2021)
For determination of the critical level and development of phosphorus fertilizer needed for canola “Brassica napus L” Hayola 401 figure based on the soil test in the dry framing 16 tests in four places and in each place 4 tests in 4 groups of phosphorus useable in the soil (less than 3 ppm, 3-6 ppm, 6-10 ppm and more than 10 ppm)p in the form of Randomized complete blocks design with 4 phosphorus fertilizer treatments (0, 25, 50, 75, kilograms of P2O5 in each acre) triple super phosphate sources were used in 4 repetition for 2 agricultural years(2008-2010). The findings indicate that the critical level of soil phosphorus to Kate - Nelson, economic outlook and the equation Mitcherlich is respectively 7, 6, 9 / 4 ppm. The fertility index degrees in phosphorous groups used in the soil have been determined as (Less than 3 ppm,3-5 ppm, 5-7 ppm and more than 7 ppm) respectively (60, 44, 25, 0 kgs P2O5 in acres).